Relationships between pre-pandemic mental health, sociodemographic factors and health behaviours in older adults during the acute onset of COVID-19 in Australia: A descriptive analysis - Nicole Lovato; Sarah L. Appleton; Amy C. Reynolds; Tiffany K. Gill; Sean Martin; Gary A. Wittert; Robert J. Adams (PLoS ONE, 2026)
Objective To gain a comprehensive understanding of associations between mental health symptoms and sociodemographic and health factors assessed during COVID-19 restrictions in existing, longitudinal community-based cohorts. Methods Participants of The North West Adelaide Health Study (NWAHS, n = 982) and the Florey Adelaide Male Ageing Study (FAMAS, n = 338) in South Australia, undertook a COVID-19 impacts survey during October 2020-May 2021. The Centre for Epidemiologic Studies Depression Scale (score≥16;NWAHS) and the Beck Depression Inventory 1A (score≥13;FAMAS) were used to characterise mild-severe depressive symptoms. The Generalised Anxiety Disorder questionnaire was used to identify moderate-severe anxiety (score 10–21). Results Of 1,320 participants (male n = 797), 62.4% (n = 824) were aged ≥65years (range 36−100 years), and 37.8% reported workforce participation at the time of the COVID-19 survey. Depressive and anxiety symptoms were observed for participants aged 35−54years (OR=1.92,95%CI = 1.01–3.67), financial stress (1.81,1.02–3.21), change in overall food intake (increase and decrease), social support none/sometimes(2.74,1.48–5.07), low control/mastery since COVID-19 (6.00,3.37–10.6) and poor sleep during restrictions (7.94,4.25–14.8), independent of previous depressive symptoms (8.30,1.9–13.2). Change in mental health status from pre-COVID to COVID-19 restriction was associated with sex (p = 0.013) and age (p < 0.001), such that females and younger participants (35−54yr) reported depressive symptoms at both times. Younger adults (35-54 yr) showed a higher prevalence of depressive symptoms only during COVID-19. Conclusions Depressive and anxiety symptoms were consistent during COVID-19 relative to pre-COVID-19. Those with a history of depression, were more likely to report depressive and anxiety symptoms during COVID-19. Government-funded initiatives employed during future pandemics should consider tailored mental health and social support for vulnerable groups.